N-glycosylation status of beta-haptoglobin in sera of patients with prostate cancer vs. benign prostate diseases - Yoon,S-J; Park,S-Y; Pang,P-C; Gallagher,J; Gottesman,JE; Dell,A; Kim,J-H; Hakomori,S-I (International Journal of Oncology, 2010)
N-glycosylation status of purified β-haptoglobin separated from sera of patients with prostate cancer was studied in comparison to that of sera from patients with benign prostate diseases, or normal subjects. Two different approaches, as summarized below, one based on binding of lectins and antibodies to β-haptoglobin, the other on mass spectrometry of released N-linked glycans from β-haptoglobin, were performed. Some of the results were useful for distinction of prostate cancer vs. benign prostate diseases. i) Binding of Phaseolus vulgaris-L lectin (PHA-L), defining the GlcNAcβ6Manα6Man side chain present in tri- or tetra-antennary N-linked glycans, to β-haptoglobin was higher for cases of prostate cancer and high-grade prostate intraepithelial neoplasia than for benign diseases. Binding of Aleuria aurantia lectin (AAL) defining Fucα3-, α4-, or α6-GlcNAc, or monoclonal antibody directed to sialyl-Lex, to β-haptoglobin was also higher for some of the cancer cases than for benign diseases. Many other lectins and antibodies showed no binding to β-haptoglobin, or showed no significant difference between cancer vs. benign diseases. ii) Mass spectrometric analysis of N-linked glycans of β-haptoglobin released by Peptide N-glycosidase-F showed enhanced expression of monosialyl tri-antennary structures in prostate cancer cases. Thus, binding of PHA-L to affinity-purified β-haptoglobin from sera of patients could lead to development of useful tools for differential diagnosis of prostate cancer vs. benign prostate diseases.